Using Learning Theory to Shape Learning Experiences in Health Care Education: Not Scary at All!. (26th June 2020) - Brown, Jo
Abstract: Whenever the word "theory" is used in association with teaching and learning people often react scared. This chapter is an attempt to dispel some myths about using learning theory in health care education in the hope that you will celebrate theory for the fascinating thing it is.